Telefoniczne załatwienie sprawy administracyjnej - Strzępek, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The possibility of settling an administrative case by telephone is a significant novelty among the adopted solutions regarding administrative procedures. The legislator considered this issue to be particularly important, creating such a possibility among the general principles of the Code of Administrative Procedure. In practice, however, problems may arise with the application of this provision, especially with regard to its hypothesis and documenting the organ’s activity in this regard. This study is an attempt to signal the most important problems that may arise in practice, at the same time indicating the potential possibilities of solving them, and contributes to discussions in this area.
Keywords: handling the case by telephone; official endorsement; contact with the party